2-Hydroxynaphthaldehyde chitosan schiff-base; new complexes, biosorbent to remove cadmium(II) ions from aqueous media and aquatic ecotoxicity against green alga Pseudokirchneriella subcapitata. Issue 2 (April 2018) - Elsayed, Shadia A.; Saad, Eman M.; Butler, Ian S.; Mostafa, Sahar I.
Graphical abstract: Highlights: Preparation of chitosan 2-hydroxynaphthaldehyde (2CS-Hhnal) Schiff-base and its complexes. Adsorption of Cd(II) ions onto 2CS-Hhnal in aqueous media. Successful removal of Cd(II) ions from wastewater. Adsorbed Cd(II) ions was determined by atomic absorption and Raman intensity of (CN) stretch. Evaluation of ecotoxicity of Pseudokirchneriella subcapitata by Cu(II), Zn(II), Pd(II), Ag(I) complexes of 2CS-Hhnal. Abstract: Chemically modified chitosan (CS) has been produced with the aim of forming a Schiff-base with 2-hydroxynaphthaldehyde (2CS-Hhnal). Complexes of 2CS-Hhnal with Ni(II), Cu(II), Zn(II), Pd(II), Ag(I), Cd(II) and Hg(II) have been synthesized and characterized by various spectroscopic methods (FT-IR, Raman, UV–vis reflectance, solid-state 13 C NMR and XRD) and morphological (SEM, EDX), elemental analysis, TGA and magnetic measurements. The morphology and structure of CS are different from those of the 2CS-Hhnal Schiff-base. In the complexes, the uninegative bidentate ligand (2CS-hnal − ) is coordinated to the metal ions through the azomethine-N and deprotonated hydroxy-O atoms without any participation from the glucose amine hydroxy-O atoms. Adsorption is considered to be a potential cost-effective method for the removal of heavy metal ions from aqueous media and by incorporating 2CS-Hhnal, we found that the adsorption of Cd(II) ions was greatly enhanced when compared to adsorption with free CS itself. The optimum experimental parameters for this process are discussed in this paper, including the initial pH, amount of sorbent, contact time and Cd(II) ion concentration. The experimental data were fitted well by a pseudo-second-order kinetics model, while the equilibrium data could be accounted for by a Langmuir model. The desorption process with EDTA and HNO3 (0.1 mol L −1 ) illustrates the regeneration ability of 2CS-Hhnal without any significant loss of its initial properties throughout three adsorption–desorption cycles. Compared to commercially expensive sorbents, the non-toxic, biodegradable 2CS-Hhnal material could prove to be an attractive, alternative material for the removal of Cd(II) ions from wastewater. The amount of Cd(II) ions adsorbed onto 2CS-Hhnal was determined by atomic absorption spectroscopy and from the intensity of the Raman-active azomethine (CN) vibration. In addition, the aquatic ecotoxicity of free 2CS-Hhnal and its complexes against green alga Pseudokirchneriella subcapitata was evaluated.